Administration of USP7 inhibitor P22077 inhibited cardiac hypertrophy and remodeling in Ang II-induced hypertensive mice - Gu, Yu-Hui; Ren, Kai-Wen; Wang, Yu; Wang, Shi-Hao; Yu, Xiao-Hong; Xu, Li-Wen; Li, Hui-Hua; Bi, Hai-Lian (Frontiers in Pharmacology, 2022)
Hypertension is one of the common causes of pathological cardiac hypertrophy and a major risk for morbidity and mortality of cardiovascular diseases worldwide. Ubiquitin-Specific Protease 7 (USP7), the first identified deubiquitinating enzymes, participated in a variety of biological processes, such as cell proliferation, DNA damage response, tumourigenesis, and apoptosis. However, its role and mechanism in cardiac remodeling remain unclear. Here, our data indicated that USP7 expression is increased during Ang II-induced cardiac hypertrophy and remodeling in mice and humans with heart failure, while the administration of its inhibitor p22077 attenuated cardiac hypertrophy, cardiac fibrosis, inflammation, and oxidase stress. Mechanistically, the administration of p22077 inhibited the multiple signaling pathways, including AKT/ERK, TGF-β/SMAD2, NF-κB/NLRP3, and NOX2/NOX4. Taken together, these findings demonstrate that USP7 may be a new therapeutic target for hypertrophic remodeling and HF.